Harmoni Kewajiban dan Hak Negara dan Warga Negara dalam Demokrasi yang Bersumbu pada Kedaulatan Rakyat dan Musyawarah - Sinaga, Diniasih Saskia; Situmorang, Jelita; M, Marcelia; Weking, Veronika Elvina (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to discuss the concept of harmony between the obligations and rights of the state and citizens in the context of democracy based on popular sovereignty and deliberation for consensus. The research method used is qualitative with secondary data analysis from various related sources. The research results show that a balance between the rights and obligations of the state and citizens is very important to create a just, stable and just society in healthy democratic practices. This research also highlights the main problem faced, namely increasing public awareness of mutual accountability in upholding the state's rights and obligations. Humans have rights that must be respected, but often ignorance results in abuse of these rights. Likewise with a person's duties and obligations towards the state; however, due to a lack of understanding, other people's rights are often violated. It is important for citizens to be aware of their rights and responsibilities in order to create a harmonious balance between obligations and rights. Thus, it is important to continue to study and understand the harmony between the obligations and rights of the state and citizens in the context of democracy based on popular sovereignty and deliberation for consensus. Only by achieving the right balance between rights and obligations can society experience justice and prosperity in democratic practice.